THE INFLUENCE OF THE INTERNET ON THE ACQUISITION OF FOREIGN CULTURES AMONG CHILDREN AND YOUNG PEOPLE - A. Alimi (Trakia Journal of Sciences, 2024)
In recent years, the usage of the internet has taken place in every corner of our country. According to many studies, the excessive use of the Internet can show some changes in the human personality, where these changes in young people are more unpredictable and more rapid. The main goal of this study is to investigate the use of the Internet and social networks by young people and children and their impact on health, behavior, and especially on the acquisition of foreign habits from other cultures. From experience with children and students, we see that every day more and more habits are acquired that do not belong to our culture, all this as a consequence of the access they have to the Internet to getto know other non-Albanian cultures. The possibilities offered by the internet and social networks nowadays make foreign culture as popular and as close as possible, thereby endangering our culture as Albanian people.An awareness of this has been introduced to me much earlier since we started enrolling children who were stuck in naming colors and numbers, not those who didn't know them, but these children only knew the name in English. In this topic we will particularly see the impact of the Internet on: The way of feeding, speaking and writing, celebrating holidays, expressing emotions as well as socialization, on children and young people. Counseling work with groups of students, parents, and teachers will help to achieve a degree of awareness of this current phenomenon.